Cuba Validated as the First Country to Eliminate Mother-to-Child Transmission of Human Immunodeficiency Virus and Congenital Syphilis: Lessons Learned from the Implementation of the Global Validation Methodology. Issue 12 (December 2016) - Caffe, Sonja; Perez, Freddy; Kamb, Mary L.; Gomez Ponce de Leon, Rodolfo; Alonso, Monica; Midy, Ralph; Newman, Lori; Hayashi, Chika; Ghidinelli, Massimo
Abstract : Implementation of the global methodology for validation of elimination of mother-to-child transmission of human immunodeficiency virus in Cuba demonstrated the feasibility of elimination of mother-to-child transmission, even in low-resourced settings, and suitability of the validation methodology.